The other is an I (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In an attempt to map out a bit of the hegemonic ideological structure today, this article investigates some works, including the play Without Words, in order to understand the ways in which they are positioned in the same set of forces. The hypothesis is that a kind of re-branding of the (neo)colonial structure of the world arts market is underway, which tends to create new ways of framing the voices of those who are positioned on the peripheries of the system, who are generally in charge of, contrary to what Paul B. Preciado proposes, bringing news from the margins. Preciado proposes, to bring news from the margins - through a certain gesture of fulfillment, which we have identified as being attributed to such voices in more than one context.
Keywords: neo-colonialism; Hal Foster; Paul B. Preciado; Without Words; 35 Bienal of São Paulo